b novel in cartoons /c - Kinney, Jeff. (b)
Being a kid can really stink. And no one knows this better than Greg Heffley, who finds himself thrust into high school where undersized weaklings share the hallways with kids who are taller, meaner, and already shaving. Luckily Greg has his best friend and sidekick, Rowley
Keywords: realistic fiction and comedy